A user's view of commercial mobile applications designed to measure hand hygiene compliance by direct observation. (November 2021) - Cawthorne, K.-R.; Oliver, C.; Cooke, R.P.D.
Summary: Background: Mobile applications (apps) that facilitate the measurement of hand hygiene (HH) compliance rates by direct observation (DO) are widely available. Their usefulness for infection prevention and control (IPC) professionals has neither been recently reviewed nor formally assessed. Aim: To present a critical analysis of hand hygiene measurement apps. Methods: Mobile apps were identified from four sources: PubMed, Apple app store, Google Play app store, Google search engine. Individual apps were then evaluated against a novel scoring system using seven key criteria considered relevant for IPC professionals. These included availability, price, automated data analysis, training requirement, compliance measured against the World Health Organization (WHO) 5 moments of HH, recent updates, and average app store rating. For each criterion, possible scores ranged from zero to two, with a maximum available score of 14 per app. Findings: A total of 32 apps were identified of which 13 were suitable for analysis. Only three apps (19%) scored ≥12. Twelve apps (92%) allowed compliance to be measured against the WHO 5 moments of HH. Five apps (38%) were completely free to use, seven apps (54%) allowed for automatic analysis and reporting of HH data and only six apps (46%) had high app store ratings. Conclusion: The current mobile apps available for DO of HH generally scored poorly. In order to make these apps more useful to IPC professionals, they should be user-friendly and require less training prior to use. National IPC organizations should develop core standards for these apps to guide future development.